Facing depression: evaluating the efficacy of the EmpkinS-EKSpression reappraisal training augmented with facial expressions – protocol of a randomized controlled trial - Marie Keinert; Lena Schindler-Gmelch; Lydia Helene Rupp; Misha Sadeghi; Klara Capito; Malin Hager; Farnaz Rahimi; Robert Richer; Bernhard Egger; Bjoern M. Eskofier; Matthias Berking (BMC Psychiatry, 2024)
Abstract Background Dysfunctional depressogenic cognitions are considered a key factor in the etiology and maintenance of depression. In cognitive behavioral therapy (CBT), the current gold-standard psychotherapeutic treatment for depression, cognitive restructuring techniques are employed to address dysfunctional cognitions. However, high drop-out and non-response rates suggest a need to boost the efficacy of CBT for depression. This might be achieved by enhancing the role of emotional and kinesthetic (i.e., body movement perception) features of interventions. Therefore, we aim to evaluate the efficacy of a cognitive restructuring task augmented with the performance of anti-depressive facial expressions in individuals with and without depression. Further, we aim to investigate to what extent kinesthetic markers are intrinsically associated with and, hence, allow for the detection of, depression. Methods In a four-arm, parallel, single-blind, randomized controlled trial (RCT), we will randomize 128 individuals with depression and 128 matched controls without depression to one of four study conditions: (1) a cognitive reappraisal training (CR); (2) CR enhanced with instructions to display anti-depressive facial expressions (CR + AFE); (3) facial muscle training focusing on anti-depressive facial expressions (AFE); and (4) a sham control condition. One week after diagnostic assessment, a single intervention of 90–120-minute duration will be administered, with a subsequent follow-up two weeks later. Depressed mood will serve as primary outcome. Secondary outcomes will include current positive mood, symptoms of depression, current suicidality, dysfunctional attitudes, automatic thoughts, emotional state, kinesthesia (i.e., facial expression, facial muscle activity, body posture), psychophysiological measures (e.g., heart rate (variability), respiration rate (variability), verbal acoustics), as well as feasibility measures (i.e., treatment integrity, compliance, usability, acceptability). Outcomes will be analyzed with multiple methods, such as hierarchical and conventional linear models and machine learning. Discussion If shown to be feasible and effective, the inclusion of kinesthesia into both psychotherapeutic diagnostics and interventions may be a pivotal step towards the more prompt, efficient, and targeted treatment of individuals with depression. Trial registration The study was preregistered in the Open Science Framework on August 12, 2022 ( https://osf.io/mswfg/ ) and retrospectively registered in the German Clinical Trials Register on November 25, 2024. Clinical Trial Number: DRKS00035577.